1999
DOI: 10.1080/026567399285558
|View full text |Cite
|
Sign up to set email alerts
|

Review Hyperthermia and liposomes

Abstract: Hyperthermia and liposomal drug delivery are treatment modalities that have been used to treat cancer over the last two decades. More recently, the two therapies have been used together in an attempt to exploit their mutual interactions against cancer. The goal of this review is to explore the literature related to combined hyperthermia and liposomal drug delivery for cancer therapy. The motivation behind combining hyperthermia and liposomal drug delivery is discussed from a physical chemical and physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Light‐absorbing photothermal agents can serve as heat carrier for local hyperthermia. Like PDT, mild hyperthermia improves vascular perfusion and enhances the extravasation of nanoparticles into the tumor interstitial space 230, 231, 232. Kong et al demonstrated that liposomal extravasation rate is affected by particle size, temperature and timing between hyperthermia and liposome administration 231.…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
“…Light‐absorbing photothermal agents can serve as heat carrier for local hyperthermia. Like PDT, mild hyperthermia improves vascular perfusion and enhances the extravasation of nanoparticles into the tumor interstitial space 230, 231, 232. Kong et al demonstrated that liposomal extravasation rate is affected by particle size, temperature and timing between hyperthermia and liposome administration 231.…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
“…It has also been proposed that physiologically-present proteins act at domain boundaries to disrupt the liposome and increase release 105 . These mechanisms would tend to favour slow, diffusive release, while the disruption in the membrane inherent to the phase transition itself could allow a transitory “burst” of release.…”
Section: Technologymentioning
confidence: 99%
“…First, by regulating physical barriers including blood flow and extravasation, the tumor vasculature limits the delivery of therapeutic agents spanning several orders of magnitude in size, including antibodies, nanoparticle carriers, and conventional chemotherapies. [3-7] Second, many solid tumors are dependent on the host vasculature for supplying nutrients and oxygen during neoangiogenesis. These features make the vasculature a generalized and genetically-stable target for solid tumors.…”
Section: Introductionmentioning
confidence: 99%